2017
DOI: 10.31233/osf.io/dt6yj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reassessment of the phylogenetic interrelationships of basal turtles (Testudinata)

Abstract: Recent discoveries from the Late Triassic and Middle Jurassic have significantly improved the fossil record of early turtles. These new forms offer a unique opportunity to test the interrelationships of basal turtles. Nineteen fossil species are added to the taxon sample of the most comprehensive morphological phylogenetic analysis of the turtle clade. Among these additional species are recently discovered forms (e.g., Odontochelys semitestacea, Eileanchelys waldmani, Condorchelys antiqua), taxa generally omit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 57 publications
(235 reference statements)
1
35
1
3
Order By: Relevance
“…This resulting "superfamilial" clade is named Chelydroidea following Baur (1893), who was the first to recognize this exact arrangement (Knauss et al 2011). Although current morphological studies still fail to retrieve a monophyletic Chelydroidea (e.g., Joyce 2007;Anquetin 2012;Sterli et al 2013;Rabi et al 2014), some compelling character evidence is nevertheless available that supports the monophyly of this clade (Knauss et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…This resulting "superfamilial" clade is named Chelydroidea following Baur (1893), who was the first to recognize this exact arrangement (Knauss et al 2011). Although current morphological studies still fail to retrieve a monophyletic Chelydroidea (e.g., Joyce 2007;Anquetin 2012;Sterli et al 2013;Rabi et al 2014), some compelling character evidence is nevertheless available that supports the monophyly of this clade (Knauss et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Joyce (2007) included an expanded sample by scoring Plesiochelys etalloni, Portlandemys mcdowelli, Jurassichelon oleronensis (his "Thalassemys" moseri), and Solnhofia parsonsi as terminal taxa, but they were found in a paraphyletic arrangement. More recent global phylogenetic analyses of turtles continued to include these species as separate terminal taxa Parham 2006, 2008;Sterli 2010;Anquetin 2012;Rabi et al 2013;Sterli et al 2013;Zhou et al 2014;Zhou and Rabi 2015), but none found them to form a monophyletic group.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…Jurassichelon oleronensis is based on a single specimen (PIMUZ A/III 514) from the Tithonian of the Isle of Oléron, France (Rieppel 1980). This specimen represents one of the few skull-shell associations known for thalassochelydians and is therefore regularly included into phylogenetic analyses (e.g., Gaffney and Meylan 1988;Joyce 2007;Sterli 2010;Anquetin 2012;Rabi et al 2013). Rieppel (1980) originally referred this specimen to Thalassemys moseri Bräm, 1965, but pointed out that this species was probably more closely related to Plesiochelys than to Thalassemys hugii.…”
Section: Jurassichelon Oleronensis Pérez-garcía 2015bmentioning
confidence: 99%
“…The pioneering studies of Hutchison and Bramble (1981) and synthesized the basal framework of kinosternoid evolution through the fossil record, and later studies have been able to add little more. These studies formed the basis for later analyses, in particular Knauss et al (2011) and Bourque et al (2014) and also informed global studies of turtle relationships (e.g., Joyce 2007;Anquetin 2012;Joyce et al 2013;Sterli et al 2013;Rabi et al 2014). Iverson (1991) in parallel provided a detailed morphological analysis that attempts to resolve the phylogenetic relationship of all extant kinosternids at the species level.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…Although numerous morphological characters exist that could unite this highly inclusive clade, named Chelydroidea following Baur (1893) , current morphological studies still fail to retrieve this clade (e.g., Joyce 2007;Anquetin 2012;Sterli et al 2013;Rabi et al 2014). Nevertheless, the fossil record is more consistent with the molecular arrangement in that all pantrionychian clades can be traced back to the Early Cretaceous of Asia, whereas all chelydroid clades only emerged during the Late Cretaceous of North America (Crawford et al 2015), and because early representatives of the chelydroid lineage are difficult to distinguish from one another.…”
Section: Introductionmentioning
confidence: 99%